Inhibition of Lipopolysaccharide-Induced iNOS and COX-2 Expression by Indole Alkaloid, 3-(Hydroxymethyl)-6,7-Dihydroindolo[2,3-a]Quinolizin-(12H)-one, via NF-κB Inactivation in RAW 264.7 Macrophages - Zhao, Feng; Chen, Lei; Zhang, Menglin; Bi, Chenchen; Li, Lichun; Zhang, Qingzhen; Shi, Cuicui; Li, Miao; Zhou, Songsong; Kong, Linghua (Planta Medica, 2013)
3-(Hydroxymethyl)-6,7-dihydroindolo[2,3-a]quinolizin-(12H)-one is a bioactive indole alkaloid isolated from Nauclea officinalis, a plant species which is used as a traditional Chinese medicine. We investigated the anti-inflammatory properties of 3-(hydroxymethyl)-6,7-dihydroindolo[2,3-a]quinolizin-(12H)-one in RAW 264.7 murine macrophages. The results indicated that it inhibited the overproduction of NO and the release of TNF-α. Furthermore, this compound inhibited the expression of iNOS and COX-2 proteins, the enzymatic activity of iNOS, and the translocation of NF-κB to the nucleus induced by LPS. Therefore, we suggested that the effect of 3-(hydroxymethyl)-6,7-dihydroindolo[2,3-a]quinolizin-(12H)-one-mediated inhibition of the expression of LPS-induced iNOS and COX-2 genes is due to the suppression of NF-κB activation in the transcriptional level.
Keywords: Nauclea officinalis; Rubiaceae; indole alkaloid; anti-inflammatory effect